Antigen-Specific Tissue-Resident Memory T Cells in the Respiratory System Were Generated following Intranasal Vaccination of Mice with BCG - Qiongli Wu; Shuangpeng Kang; Jun Huang; Shunqiao Wan; Binyan Yang; Changyou Wu (Journal of Immunology Research)
Tissue-resident memory T cells (TRM) are different from effector memory T cells (TEM) and central memory T cells (TCM) and contribute to the protective immunity against local challenges. Currently, we found that CD4+ and CD8+ TRM cells in the nasal mucosa, trachea, lungs, and lavage fluids were heterogeneous on the expression of CD69 and CD103 as well as the production of cytokines including IFN-γ, IL-2, and TNF-α. After intranasal vaccination of mice with BCG, respiratory tissues expressed higher levels of the chemokine CXCL16 and TRM cells expressed CXCR6 to CXCL16. In addition, antigen-specific CD4+ and CD8+ TRM cells expressed cytokines following the stimulation with BCG and persisted in the nasal mucosa, trachea, and lungs for more than a hundred days. At the same time, mice were infected intranasally with live BCG and the results showed that vaccinated mice cleared up live BCG faster than nonvaccinated mice in the respiratory system. Taken together, our data demonstrated that intranasal vaccination of mice with BCG could induce antigen-specific CD4+ and CD8+ TRM cells in the respiratory system and have the ability to provide protection against pulmonary reinfection.